UTTERANCES OF ALAN TURING AND THE EFFECT TOWARD OTHER CHARACTERS IN THE IMITATION GAME MOVIE - I Wayan Juniartha; I Putu Gita Rusmana (LPPM Universitas Dhyana Pura, 2019)
ABSTRACTCommunication whether one way or two ways tends to have intention that needs to beconvey to hearer from the speaker. Furthermore, to what extend the intention can beunderstood it is based on the context that can acknowledged by sides, the speaker and hearer.Movie, as one of the media to show how context-based communication conducted, reflectsthe communication of the speaker whether it is understood by the hearer. This articleformulates the utterances of the main character in The Imitation Game movie and the effectof it to the hearer which theoretically known as illocutionary act and perlocutionary act. Themethod used in collecting data is observation method, while in analyzing the data,qualitative method is used. The theory used are the theory by Leech (1983) and Searle(1979); and supported by Austin (1962). It is found that all of type of directive illocutionaryact, as ordering, asking, requesting and prohibiting, is found in the utterances and all of theutterances lead in into the act of the hearer in giving reaction upon the utterance, whether itis supporting the intention or not.Keywords: utterances, illocutionary act, perlocutinary act, main character, movie.ABSTRAKKomunikasi, baik itu satu arah ataupun dua arah cenderung mempunyai maksud yang ingindisampaikan ke pendengarnya dari seorang pembicara. Sejauh mana maksud itu dipahamitergantung terhadap konteks yang dapat dipahami oleh kedua belah pihak, pembicara danpendengarnya. Film, sebagai satu media yang menunjukkan bagaimana komunikasiberlandaskan konteks dilakukan, mencerminkan komunikasi yang dilakukan olehpembicara kepada pendengarnya, dipahami atau tidak. Artikel ini mengangkat ujaran yangdiucapkan oleh karakter utama dalam film The Imitation Game dan efek yang diberikandari ujaran tokoh utama kepada pendengarnya, secara teor dsebut dengan tindak ilokusidan tidak perlokusi. Metode yang digunakan dalam mengoleksi data adalah metodeobservasi, sementara dalam menganalisa data digunakan metode kualitatif. Theori yangdigunakan adalah teory yang dikemukakan oleh Leech (1983) dan Searle (1979); dan jugateori pendukung oleh Austin (1962). Dapat diketahui bahwa semua tipe tindak ilokusidirektif, yaitu ordering, asking, requesting, dan prohibiting datemukan dalam ujaran padakarakter utama. Ujaran tersebut berpengaruh terhadap tindakan dari pendengar dalambereaksi terhadap ujaran itu, baik itu memmenuhi maksud dari pendengar atau tidak.Kata kunci: ujaran, tidak ilokusi, tindak perlokusi, karakter utama, film.